3D Printing Aids Acetabular Reconstruction in Complex Revision Hip Arthroplasty. (10th January 2017) - Hughes, Andrew J.; DeBuitleir, Cathal; Soden, Philip; O'Donnchadha, Brian; Tansey, Anthony; Abdulkarim, Ali; McMahon, Colm; Hurson, Conor J.
Abstract : Revision hip arthroplasty requires comprehensive appreciation of abnormal bony anatomy. Advances in radiology and manufacturing technology have made three-dimensional (3D) representation of osseous anatomy obtainable, which provide visual and tactile feedback. Such life-size 3D models were manufactured from computed tomography scans of three hip joints in two patients. The first patient had undergone multiple previous hip arthroplasties for bilateral hip infections, resulting in right-sided pelvic discontinuity and a severe left-sided posterosuperior acetabular deficiency. The second patient had a first-stage revision for infection and recurrent dislocations. Specific metal reduction protocols were used to reduce artefact. The images were imported into Materialise MIMICS 14.12®. The models were manufactured using selective laser sintering. Accurate templating was performed preoperatively. Acetabular cup, augment, buttress, and cage sizes were trialled using the models, before being adjusted, and resterilised, enhancing the preoperative decision-making process. Screw trajectory simulation was carried out, reducing the risk of neurovascular injury. With 3D printing technology, complex pelvic deformities were better evaluated and treated with improved precision. Life-size models allowed accurate surgical simulation, thus improving anatomical appreciation and preoperative planning. The accuracy and cost-effectiveness of the technique should prove invaluable as a tool to aid clinical practice.